Von der Innovation zur Institution Institutionalisierungsarbeit an Hochschulen am Beispiel der Leitung von Schreibzentren - Girgensohn, Katrin (W. Bertelsmann Verlag, 2017)
The author asks about the institutional and personal conditions under which academic writing centres can be established in the long term. As an example, she analyses the situation at universities in the USA, where problems are similar to those in Germany: lack of acceptance, lack of financial provision and unclear expectations. Expert interviews with directors of writing centres serve as the empirical basis. The focal point of the investigation is institutionalisation work at management level that is equally characterised by intentional and accidental actions, successes and failures. The result is a model for institutionalisation work by writing centre directors, as well as recommendations for actions that are transferrable to the establishment of writing centres and other innovative institutions at German universities.